2014
DOI: 10.3389/fonc.2014.00175
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Reversed Obesity-Induced HGF/c-Met Pathway and Basal-Like Breast Cancer Progression

Abstract: Epidemiologic studies demonstrate that obesity is associated with an aggressive subtype of breast cancer called basal-like breast cancer (BBC). Using the C3(1)-TAg murine model of BBC, we previously demonstrated that mice displayed an early onset of tumors when fed obesogenic diets in the adult window of susceptibility. Obesity was also shown to elevate mammary gland expression and activation of hepatocyte growth factor (HGF)/c-Met compared to lean controls, a pro-tumorigenic pathway associated with BBC in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 62 publications
1
42
0
Order By: Relevance
“…And an experiment using the C3(1)-T Ag murine model demonstrated that weight loss could prevent basal-like breast cancer by blocking the obesity-responsive pro-tumorigenic hepatocyte growth factor/c-Met pathway 41 . Thus, theoretically, obesity may increase both luminal and triple-negative tumor risk in premenopausal and postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…And an experiment using the C3(1)-T Ag murine model demonstrated that weight loss could prevent basal-like breast cancer by blocking the obesity-responsive pro-tumorigenic hepatocyte growth factor/c-Met pathway 41 . Thus, theoretically, obesity may increase both luminal and triple-negative tumor risk in premenopausal and postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Digital images of stained sections were generated by scanning slides using an Aperio Image Scope Digital Slide Scanner (Vista, CA). Total positive DAB staining was quantified in 5 random microscopic fields using Aperio ImageScope Software (Vista, CA and [6,9]).…”
Section: Methodsmentioning
confidence: 99%
“…While the majority of preclinical studies randomize mice to CR from the outset, two preclinical studies have specifically tested the impact of diet-induced obesity followed by weight loss, by incorporating a diet switch during the intervention period. Interestingly, these studies reported contrasting findings, with one reporting that weight loss reversed the tumor-promoting effect of obesity (Sundaram, et al 2014b), and the other reporting the weight loss did not impact obesity-fueled tumor growth (De Angel, et al 2013). Key differences between studies included the degree of obesity attained by the mice and the timing and duration of weight loss, in addition to the use of two different mouse models of basal-like breast cancer, one xenograft (De Angel et al 2013) and the other transgenic (Sundaram et al 2014b).…”
Section: Obesity and Related Co-morbidities As Modifiable Lifestylmentioning
confidence: 99%
“…Interestingly, these studies reported contrasting findings, with one reporting that weight loss reversed the tumor-promoting effect of obesity (Sundaram, et al 2014b), and the other reporting the weight loss did not impact obesity-fueled tumor growth (De Angel, et al 2013). Key differences between studies included the degree of obesity attained by the mice and the timing and duration of weight loss, in addition to the use of two different mouse models of basal-like breast cancer, one xenograft (De Angel et al 2013) and the other transgenic (Sundaram et al 2014b). Discrepant findings such as these may shed light on mechanisms linking weight loss and breast cancer, in addition to informing future study design in both preclinical mouse models and humans.…”
Section: Obesity and Related Co-morbidities As Modifiable Lifestylmentioning
confidence: 99%